A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China - Ai, Deqiang; Wang, Yinglun; Zhang, Yalin (Zootaxa, 2019)
This paper describes one new flatid genus, Armorseliza gen. nov., two new species and one new combination. This new genus is assigned to the tribe Selizini. A key to genera and a checklist of all known species of the tribe Selizini from China are provided.